PERANAN IBU RUMAH TANGGA PETANI KARET DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA (Studi Kasus Di Desa Kuapan Kecamatan Tambang Kabupaten Kampar) - Ruliana Kusuma Astuti; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
work and propose household is difficult. Work bugged rubber many difficulty and challenges from the community, also derision of thed community. But there are still many women who do work bugged rubber in Desa Kuapan. The purpose of this research is describe social and economic conditions rubber famers family existing in Desa Kuapan Kecamatan Tambang Kabupaten Kampar Provinsi Riau. Described the role of mothers tappers in arranging households in Desa Kuapan Kecamatan Tambang Kabupaten Kampar Provinsi Riau. To identify the constraints experienced mother tappers rubber in arranging households anf the breadwinner. To know the role of mother tappers rubber in improving the welfare of economic family. Methods used was a qualitative methodology to technique interview to collect data and information. The result of the study found that social and economic conditions of a family mothers tappers rubber increase after they had trade bugged rubber with an indicator fulfill their daily needs and also they can sending their children to school. The role of mothers rubber tappers in improving the welfare of the family performed with : a). tale wages bugged rubber to add to the family income, b). to setting aside income saved to their family needs.keyword : housewives, tappers rubber, welfare